2018
DOI: 10.1111/jdv.15171
|View full text |Cite
|
Sign up to set email alerts
|

A randomized, double‐blind controlled study of the efficacy and safety of topical solution of 0.25% finasteride admixed with 3% minoxidil vs. 3% minoxidil solution in the treatment of male androgenetic alopecia

Abstract: Treatment with topical solution of 0.25% finasteride admixed with 3% minoxidil was significantly superior to 3% minoxidil solution for promoting hair growth in male androgenetic alopecia, and well tolerated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
53
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(74 citation statements)
references
References 27 publications
1
53
0
4
Order By: Relevance
“…Several studies performed on Asians reported a lower prevalence of AGA and FPHL compared with the Europeans. [49][50][51][52] The development of AGA in Japanese men is approximately 10 years slower than that in Europeans, with 1.4-times lower in prevalence in each decade. 51 By contrast, the prevalence of AGA in Thais is higher and relatively similar to Caucasians, suggesting that the prevalence may be influenced by various genetic backgrounds.…”
Section: Non-scarring Alopecias In Asiansmentioning
confidence: 99%
“…Several studies performed on Asians reported a lower prevalence of AGA and FPHL compared with the Europeans. [49][50][51][52] The development of AGA in Japanese men is approximately 10 years slower than that in Europeans, with 1.4-times lower in prevalence in each decade. 51 By contrast, the prevalence of AGA in Thais is higher and relatively similar to Caucasians, suggesting that the prevalence may be influenced by various genetic backgrounds.…”
Section: Non-scarring Alopecias In Asiansmentioning
confidence: 99%
“…The effect of a topical solution of 0.25% finasteride on scalp dihydrotestosterone (DHT) in men with AGA suggested that sexual side‐effects would be minimized compared with oral finasteride . A topical solution of 0.25% finasteride admixed with 3% minoxidil tested in 40 men with AGA was reported to be significantly superior to minoxidil alone in improving hair density, hair diameter and global photographic assessment . About 90% of patients treated with the combined solution experienced moderate to marked improvement with minimal effect on plasma DHT levels and no systemic adverse events.…”
Section: Key Issues In Hair Loss: From Physiology To Treatmentmentioning
confidence: 99%
“…Although the exact molecular mechanisms are not fully understood, an abnormal level of dihydrotestosterone (DHT), a potent androgen, appears to be an important causative factor 1,2. Indeed, the upregulation of the 5α‐reductase enzyme is required to convert testosterone into DHT and is a drug target 3,4…”
Section: Introductionmentioning
confidence: 99%
“…Currently, only two treatments have been approved by the US Food and Drug Administration for the treatment of male AGA5: finasteride, a 5α‐reductase inhibitor3,6,7 administrated at 1 mg daily, and topical minoxidil (MXD) formulations (2% solution, 5% solution, or 5% foam). The effectiveness of both drugs in improving the symptoms of the disease has been demonstrated in several well‐designed studies 8,9.…”
Section: Introductionmentioning
confidence: 99%